Cardiotoxicity of radiation therapy in esophageal cancer - Vošmik, Milan; Hodek, Miroslav; Buka, David; Sýkorová, Petra; Grepl, Jakub; Paluska, Petr; Paulíková, Simona; Sirák, Igor (Reports of practical oncology and radiotherapy, 2020)
With a development of radiotherapeutic techniques, availability of radiotherapy data on cardiotoxicity, and slowly improving esophageal cancer outcomes, an increasing emphasis is placed on the heart protection in radiation treated esophageal cancer patients. Radiation induced heart complications encompass mainly pericardial disease, cardiomyopathy, coronary artery atherosclerosis, valvular heart disease, and arrhythmias. The most frequent toxicity is pericardial effusion which is usually asymptomatic in the majority of patients. The use of modern radiotherapy techniques is expected to reduce the risk of cardiotoxicity, although this expectation has to be confirmed by clinical data.
Keywords: Cardiac toxicity; Esophageal cancer; Radiation therapy